Emerging Risks of Amanita Muscaria: Case Reports on Increasing Consumption and Health Risks - Savickaitė, Emilija; Laubner-Sakalauskienė, Gabija (Acta medica Lituanica, 2025)
Introduction: The increasing popularity of Amanita muscaria, driven by its hallucinogenic properties, has raised significant public health concerns, particularly as it remains largely unregulated across most European Union countries. The mushroom contains muscimol, a compound that induces euphoria, altered perception, and hallucinations, and its precursor, ibotenic acid, converts to muscimol when dried or heated, reducing toxicity while preserving psychoactive effects. The growing trend in intentional consumption of A. muscaria reflects evolving patterns of intoxication despite its known toxicity risks. The European Food Safety Authority has flagged A. muscaria as an emerging risk, highlighting concerns over its increasing availability and potential for misuse.Materials and Methods: Four cases of Amanita muscaria consumption and subsequent intoxication have been documented in Lithuania in 2023. To further investigate this topic, a systematic search was conducted using the PubMed database with the following keyword combinations: ‘Amanita muscaria’, ‘Amanita muscaria toxicity’, ‘muscimol’, ‘ibotenic acid’, ‘psilocybin’, and ‘hallucinogenic fungi’. After screening for relevance and eligibility, a total of 27 publications met the inclusion criteria and were incorporated into the final analysis.Case Reports: In 2023, four cases of intentional A. muscaria poisoning were reported in Lithuania, linked to recreational consumption. Symptoms included tremors, respiratory failure, dizziness, and paranoia. All patients were male and required hospitalization, but all were discharged in stable condition.Conclusion: The unregulated status and increasing accessibility of A. muscaria pose significant public health concerns. While A. muscaria remains largely unstudied in medical contexts, its toxicity risks are well-documented. Misleading online information contributes to uninformed consumption, especially among younger individuals. Further research is needed to elucidate its chemical composition, therapeutic potential, and health effects to inform regulatory policies.